Evaluation of Structure and Properties of COR 13/4 (GX4CrNi13-4) Tungsten Inert Gas-Welded Steel - Bricín, David; Kříž, Antonín; Jansa, Zdeněk; Špirit, Zbyněk; Strejcius, Josef; Beňasová, Hana; Pakula, Daniel; Kolařík, Ladislav; Svobodová, Jaroslava; Knaislová, Anna (Journal of materials engineering and performance, 2025)
The effect of tungsten inert gas welding in combination with high alloyed filler materials on the microstructure and mechanical properties of COR 13/4 martensitic stainless steel were investigated by mechanical testing and metallography observation. The experimental results showed that using filler materials with higher Cr and Cr-Mo content increased the δ-ferrite content in the fusion zone. Higher Ni and N content in the filler material led to an increase in the retained austenite content in the heat-affected zone (HAZ). Higher C concentration in filler material then led to dramatically reduced impact toughness of the weld due to embrittlement of martensite structure and the presence of M 23 C 6 and σ phase in the weld and along the fusion line. The phase composition close to the fusion zone affected the wear rate, tensile properties and hardness. The results show a lower wear rate for samples with a lower amount of martensite and a higher amount of Fe 9.7 Mo 0.3 and Fe 10.8 Ni. The ultimate tensile strength (UTS) results show that the presence of the Fe 9.7 Mo 0.3 or Fe 10.8 Ni phase in HAZ contributed to an increase in the UTS value compared with the presence of the martensite phase.